Making impact investment a financing solution for African businesses - (:unkn) unknown (My University, 2024)
In the face of climate and social challenges, the financial sector can no longer limit itself to an approach focused solely on profitability. Two movements are converging. On the one hand, more and more players are calling for the extra-financial impact of investments to be taken into account in their strategy. International regulations, such as the ISSB and the CSRD, are putting increasing pressure on companies to do so. On the other hand, development financiers (governments, foundations, international financial institutions) are looking for innovative ways to accelerate growth in poor countries and contribute to global public goods through the private sector.
Keywords: African Research